Identification of impacts of climate change and direct human activities on streamflow in Weihe River Basin in Northwest China - Jingjing, Fan; Qiang, Huang; Dengfeng, Liu (International Journal of Agricultural and Biological Engineering, 2017)
Climate change and human activities make major influences on hydrology, which are known to have important impacts on streamflow variation. Therefore, it is critically important to identify how climate change and human activities will impact streamflow variation. Thus, the goal of this study is to identify the impacts of climate change and direct human activities on annual streamflow at four hydrologic stations in the Weihe River basin of China, with the estimation of evaporation based on the Budyko hypothesis. The Mann-Kendall test was employed to detect the break points of the four stations. According to the occurrence time of break points, the data series were divided into two periods: pre-change period (1960-1984) and post-change (1985-2010) period. The parameter of one-parameter Budyko-type model was calibrated with observed data during the pre-change period, with the R2 values ranged from 0.95 to 0.97 and the NSE values ranged from 0.80 to 0.94, and the high R2 and Nash-Sutcliffe Efficiency coefficient shows the model has good performance. The contribution ratios of climate change impacts on decreasing streamflow were 37%, 23%, 57% and 43%, and those of the impacts of direct human activities were 63%, 77%, 43% and 57% for the Linjiacun, Xianyang, Lintong and Huaxian station, respectively. Both the climate change and direct human activities have positive impacts on streamflow decrease at all of the four stations, and the direct human activities are the main factor causing the decrease of annual streamflow. Keywords: streamflow, climate change; human activities; evaporation, hydrological cycle, watershed, Budyko hypothesis, Weihe River basin DOI: 10.25165/j.ijabe.20171004.2313 Citation: Fan J J, Huang Q, Liu D F. Identification of impacts of climate change and direct human activities on streamflow in Weihe River Basin in Northwest China. Int J Agric & Biol Eng, 2017; 10(4): 119–129.